Nanodiamond Films for Applications in Electrochemical Systems - A. F. Azevedo; M. R. Baldan; N. G. Ferreira (International Journal of Electrochemistry)
The purpose of the present paper is to give an overview on the current development status of nanocrystalline diamond electrodes for electrochemical applications. Firstly, we describe a brief comparison between the general properties of nanocrystalline diamond (undoped and boron-doped) and boron-doped microcrystalline diamond films. This is followed by a summary of the nanodiamond preparation methods. Finally, we present a discussion about the undoped and boron-doped nanocrystalline diamond and their characteristics, electrochemical properties, and practical applications.